Pharmacological modulation of fish-induced depth selection in D. magna: the role of cholinergic and GABAergic signalling - Juliette Bedrossiantz (Nature Portfolio, 2021)
Abstract Animal behaviour is closely related to individual fitness, which allows animals to choose suitable mates or avoid predation. The central nervous system regulates many aspects of animal behaviour responses. Therefore, behavioural responses can be especially sensitive to compounds with a neurodevelopmental or neurofunctional mode of action. Phototactic behavioural changes against fish in the freshwater crustacean Daphnia magna have been the subject of many ecological investigations. The aim of this study was to identify which neurotransmitter systems modulate phototactic behaviour to fish kairomones. We used a positive phototactic D. magna clone (P132,85) that shows marked negative phototactism after exposure to fish kairomones. Treatments included up to 16 known agonists and antagonists of the serotonergic, cholinergic, dopaminergic, histaminergic, glutamatergic and GABAergic systems. It was hypothesized that many neurological signalling pathways may modulate D. magna phototactic behaviour to fish kairomones. A new custom-designed device with vertically oriented chambers was used, and changes in the preferred areas (bottom, middle, and upper areas) were analysed using groups of animals after 24 h of exposure to the selected substance(s). The results indicated that agonists of the muscarinic acetylcholine and GABAA receptors and their equi-effective mixture ameliorated the negative phototactic response to fish kairomones, whereas antagonists and their mixtures increased the negative phototactism to fish kairomones. Interestingly, inhibition of the muscarinic acetylcholine receptor abolished positive phototaxis, thus inducing the phototactic response to fish kairomones. Analysis of the profile of neurotransmitters and their related metabolites showed that the D. magna behavioural responses induced by fish depend on changes in the levels of acetylcholine, dopamine and GABA.